Learning Direction Theory and the Winner s Curse - Reinhard Selten; Klaus Abbink; Ricarda Cox (University of Bonn, Bonn Graduate School of Economics (BGSE), 2001)
We report an experiment on a decision task by SAMUELSON and BAZERMAN (1985). Subjects submit a bid for an item with an unknown value. A winner's curse phenomenon arises when subjects bid too high and make losses. Learning direction theory can account for this. However, other influences on behaviour can also be identified. We introduce impulse balance theory to make quantitative predictions on the basis of learning direction theory. We also look at monotonic ladder processes. It is shown that for this kind of Markov chains the impulse balance point is connected to the mode of the stationary distribution.
Keywords: C91; D81; D83; 330; Experimental economics; learning; individual decision making